Estimation of Multiflier Effect of Public Spending on Economic Growth under Multiple Regimes Regime - Raghu Bir Bista (PT Mattawang Mediatama Solution, 2023)
The paper estimates the multiplier effect of public spending (total government spending) on economic growth (RGDP) from 44 years long time-series database of macro-economic variables from 1974-75 to 2018-19 (Panchayat Regime (1975-1990), Democracy I: Ceremonial Monarch (1991-2005) and Democracy II: Federal (2006-2019)) through structure vector auto-regressive (SVAR) model with tests. The paper provides the above three political regimes based on relationships between public spending and economic growth and the multiplier of public spending on economic growth. As a result, in the three different regimes, their nature, behavior, and dynamics are stationary. Except for real regular spending (RRS) in Democracy I: Ceremonial Monarch (1991-2005) and real capital spending (RCS) in Democracy II: Federal (2006-2019), all coefficient values of SVAR estimate shows a significantly positive relationship between the government spending and economic growth. It indicates a positive multiplier effect of public spending; recurrent spending and capital spending are positive to economic growth, except for GRRE in Democracy I: Ceremonial Monarch (1991-2005) and RCS in Democracy II: Federal (2006-2019). Likewise, in the different political regimes, higher multiplier of total public spending, regular public spending and capital public spending in the Panchayat Regime (1975-1990) are better than successive democratic regimes so-called the people’s centric political regimes: Democracy I: Ceremonial Monarch (1991-2005) and Democracy II: Federal (2006-2019). Besides, except for the Panchayat Regime (1975-1990), the multiplier value of public spending; recurrent spending, and capital spending are lower in Democracy I: Ceremonial Monarch (1991-2005) and then Democracy II: Federal (2006-2019). It indicates the low efficiency of the government spending and budgetary system. Therefore, the government should improve the efficiency of public spending, the ratio of the capital spending, and private investment for improving the higher multiplier variable in long run.